1986
DOI: 10.1590/s0006-87051986000200001
|View full text |Cite
|
Sign up to set email alerts
|

Parcelamento da cobertura nitrogenada do algodoeiro

Abstract: RESUMO São relatados e discutidos resultados de produção obtidos em vinte e quatro ensaios de adubação com o algodoeiro, conduzidos em diferentes solos das principais áreas produtoras paulistas de 1975 a 1984. Para avaliar o efeito da adubação nitrogenada, doses de 0, 25 e 50kg/ha de N foram fornecidas em cobertura logo após o desbaste, 30 a 40 dias após a emergência das plantas. Em três outros tratamentos, a dosagem de 50kg/ha de N foi parcelada, sendo fornecida metade no desbaste e metade em fases posteriore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results were similar to those obtained and recommended by Anselmo & Leal (2010), by emphasizing that narrow row cotton does not require application of nitrogen rates different from the ones of conventional cotton, and applications up to 112 kg ha -1 N are sufficient to achieve maximum yield. In the same vein, Silva et al (1986), studying nitrogen fertilization in conventional cotton plant, found a productivity increase up to the rate of 88 kg ha -1 N. However, due to the large influence of climate conditions on cotton production, the economic N rate to be adopted depends on the productive potential of culture. Anselmo et al (2011), comparing four different sowing seasons in narrow row system, found satisfying answers in narrow row cotton productivity in the region of Chapadões when sown until end of January.…”
Section: Resultsmentioning
confidence: 99%
“…The results were similar to those obtained and recommended by Anselmo & Leal (2010), by emphasizing that narrow row cotton does not require application of nitrogen rates different from the ones of conventional cotton, and applications up to 112 kg ha -1 N are sufficient to achieve maximum yield. In the same vein, Silva et al (1986), studying nitrogen fertilization in conventional cotton plant, found a productivity increase up to the rate of 88 kg ha -1 N. However, due to the large influence of climate conditions on cotton production, the economic N rate to be adopted depends on the productive potential of culture. Anselmo et al (2011), comparing four different sowing seasons in narrow row system, found satisfying answers in narrow row cotton productivity in the region of Chapadões when sown until end of January.…”
Section: Resultsmentioning
confidence: 99%